Weight status change from birth to childhood and the odds of high blood pressure among Chinese children - Cheng Li; Ziqi Liu; Min Zhao; Cheng Zhang; Pascal Bovet; Bo Xi (Frontiers Media S.A., 2023)
BackgroundIt is well documented that birth weight and childhood weight are associated with the blood pressure (BP) levels in childhood. However, the impact of weight status change from birth to childhood on BP among children is less well described. We aimed to assess the association between changes in weight status from birth to childhood and high BP in childhood.Methods and resultsData were obtained from a cross-sectional survey conducted in Jinan, China, and a total of 5,546 children aged 6-17 years were included in this study. Based on the birth weight status [high weight (> 4,000 g) vs. normal weight (2,500-4,000 g)] and childhood weight status during the survey period [high weight (overweight and obesity) vs. normal weight], children were assigned into four groups: persistently normal weight (normal birth weight and normal childhood weight), resolved high weight (high birth weight but normal childhood weight), incident high weight (normal birth weight but high childhood weight), and persistently high weight (high birth weight and high childhood weight). After adjustment for sex and age, BP in childhood was more responsive to current body mass index (BMI) than birth weight. After adjustment for the potential covariates, compared with children who had persistently normal weight from birth to childhood, those with incident high weight (odds ratio [OR] = 3.88, 95% confidence interval [CI] = 3.29-4.57) and persistently high weight (OR = 3.52, 95% CI = 2.71-4.57) were associated with the increased odds of childhood high BP. However, children who had resolved high weight did not have significantly increased odds of high BP in childhood (OR = 0.86, 95% CI = 0.59-1.25).ConclusionThe association of BP with recent BMI was stronger than with birth weight. Children who had incident or persistently high weight from birth to childhood had increased odds of high BP in childhood, whereas the odds was not significantly increased among those with high birth weight but changed to normal weight in childhood. Our findings highlight the importance of maintaining an appropriate weight in the early lifetime for the prevention of high BP and other related diseases, especially for those with high birth weight.